Evaluation of Morpho-Physiological Traits Adjustment of Prosopis tamarugo Under Long-Term Groundwater Depletion in the Hyper-Arid Atacama Desert - Garrido, Marco; Silva, Herman; Franck, Nicolás; Arenas, Jorge; Acevedo, Edmundo (Frontiers in Plant Science, 2018)
Water extraction from the underground aquifers of the Pampa del Tamarugal (Atacama Desert, Chile) reduced the growing area of Prosopis tamarugo, a strict phreatofic species endemic to northern Chile. The objective of this work was to evaluate the effect of various architectural and morpho-physiological trait adjustments of P. tamarugo subjected to three groundwater depletion intervals (GWDr): <1m (control), 1-4m and 6-9m. The traits were evaluated at three levels, plant (height, trunk cross-section area, leaf fraction (ƒGCC), and crown size), organ (length of internodes, leaf mass per unit area (LMA), lleaflet mass and area), and tissue level (wood density (WD), leaf 13C, 18O isotope composition (δ), and intrinsic water use efficiency (iWUE)). In addition, soil water content (VWC) to 1.3 m soil depth, pre-dawn and midday water potential difference (ΔѰ), and stomatal conductance (gs) were evaluated. At the deeper GWDr, P. tamarugo experienced significant growth restriction and reduced ƒGCC, the remaining canopy had a significantly higher LMA associated with smaller leaflets. No differences in internode length and WD were observed. Values for δ13C and δ18O indicated that as GWDr increased, iWUE increased as a result of partial stomata closure with no significant effect on net assimilation over time. The morpho-physiological changes experienced by P. tamarugo allowed it to acclimate and survive in a condition of groundwater depletion, keeping a functional but diminished canopy. These adjustments allowed maintenance of a relatively high gs; ΔѰ was not different among GWDrs despite smaller VWC at greater GWDr. Although current conservation initiatives of this species are promising, forest deterioration is expected continue as groundwater depth increases.